Realization of Journalist Competency Standards at Young UKW PWI Central Sulawesi - Fery, Fery; Ahmad Yani; Andi Famrizal (Universitas Muhammadiyah Palu, 2024)
This research aims to determine the standards of understanding and competence of journalists in increasing the capacity and professionalism of journalists, especially the category of young journalists. Currently, through Press Council decision Number 01/Peraturan-DP/X/2018 concerning Journalist Competency Standards, journalists are required to continue to improve their knowledge, skills and quality of work. All journalists are expected to undergo the journalist competency test (UKW) process in a tiered manner starting from the young, middle and main journalist categories. This type of research is descriptive qualitative, data collection methods are observational studies, interviews, documentation and data analysis techniques. The results of the research show that journalists who are members of PWI are required to take part in UKW in stages. UKW which has been held by PWI Central Sulawesi has been held since 2014. Journalists who have taken part in UKW have increasingly better quality, especially regarding the credibility, capacity and reputation of PWI journalists. However, it turns out that stakeholders have not fully implemented or seen journalists who were invited to an activity based on the competency of the UKW results.